2009
DOI: 10.1007/s11105-009-0104-5
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic Analysis of Somatic Embryogenesis in Cyclamen persicum Mill

Abstract: Cyclamen persicum Mill. is a widely grown ornamental species that is clonally propagated by somatic embryogenesis. To better understand the biology of somatic embryo development in C. persicum, detailed proteomic (two-dimensional gel electrophoresis) and mass spectrometric analyses of somatic embryos at globular, torpedo, and germinating stages of development, along with nonembryogenic callus and zygotic embryos, were conducted. Of~460 proteins resolved in two-dimensional gels, 35 proteins were differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The experimental samples were isoelectrofocused together in the same run to reduce technical variability. The IPG strips were then incubated in 4 mL of equilibration buffer [6 M urea, 30% (w/v) glycerol, 2% (w/v) sodium dodecyl sulphate (SDS), 0.002% (w/v) bromophenol blue, 50 mM Tris-HCl, pH 8.8] containing 1% (w/v) DTT for 15 min and subsequently in 4 mL of the same buffer containing 2.5% (w/v) iodoacetamide (IAA) for 15 min and subjected to SDS polyacrylamide gel electrophoresis in a 12.5% polyacrylamide gel adopting the running conditions reported in Bian et al (2010). The 2-DE gels were stained with Sypro Ruby (BioRad's) following manufacturer's instructions.…”
Section: -De Analysismentioning
confidence: 99%
“…The experimental samples were isoelectrofocused together in the same run to reduce technical variability. The IPG strips were then incubated in 4 mL of equilibration buffer [6 M urea, 30% (w/v) glycerol, 2% (w/v) sodium dodecyl sulphate (SDS), 0.002% (w/v) bromophenol blue, 50 mM Tris-HCl, pH 8.8] containing 1% (w/v) DTT for 15 min and subsequently in 4 mL of the same buffer containing 2.5% (w/v) iodoacetamide (IAA) for 15 min and subjected to SDS polyacrylamide gel electrophoresis in a 12.5% polyacrylamide gel adopting the running conditions reported in Bian et al (2010). The 2-DE gels were stained with Sypro Ruby (BioRad's) following manufacturer's instructions.…”
Section: -De Analysismentioning
confidence: 99%
“…We did not observe the unique differences in the number of produced protein spots between stage III, VI and VII with the number about 545. In the case of Cyclamen persicum, studies revealed that the differing number of spots between particular stages is not large, and globular somatic embryo stage was characterized by 451 protein spots while the torpedo stage was characterized by 460 protein spots [11].…”
Section: Number Of Protein Spots Produced By Two-dimensional Electropmentioning
confidence: 99%
“…For both extreme stages, some proteins had acid character just about pH 4.0 or a base character just between pH values ranging from 9 to 10. Globular and torpedo somatic embryos of C. persicum presented IEF of proteins ranging pH 5-8, only [11].…”
Section: Proteomics Of Somatic Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, proteomic studies of SE in several species have created protein profiles of cultures in different conditions during the induction of embryogenic potential (Varhanikova et al 2014;Correia et al 2012;Marsoni et al 2008;Sharifi et al 2012;Almeida et al 2012;Guzman-Garcia et al 2013). These studies have been followed up with the focused identification of key proteins associated with each stage of the transdifferentiation of somatic embryos (Rode et al 2012;Bian et al 2010;Vale Ede et al 2014). Moreover, the morphological and physiological similarities between zygotic and somatic embryogenesis have suggested similar biochemical status for cells undergoing both of these processes, and protein profiles for zygotic and somatic embryogenesis have been compared in a few plants species (Sghaier-Hammami et al 2009;Winkelmann et al 2006;Noah et al 2013).…”
Section: Introductionmentioning
confidence: 99%